2012
DOI: 10.1002/ajmg.b.32097
|View full text |Cite
|
Sign up to set email alerts
|

An association and haplotype analysis of porcine maternal infanticide: A model for human puerperal psychosis?

Abstract: An association analysis using the Illumina porcine SNP60 beadchip was performed to identify SNPs significantly associated with porcine maternal infanticide. We previously hypothesised that this was a good animal model for human puerperal psychosis, an extreme form of postnatal mood disorder. Animals were selected from carefully phenotyped unrelated infanticide and control groups (representing extremes of the phenotypic spectrum), from four different lines. Permutation and sliding window analyses and an analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The FAM135B gene is located in chromosome 8 and has been reported to be differentially expressed in healthy people with tuberculosis (27), mental illness (39) and autism (40). To the best of our knowledge, Song et al (14) first reported that the FAM135B gene is a tumor-associated gene for esophageal cancer, by whole-genome sequencing and other technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The FAM135B gene is located in chromosome 8 and has been reported to be differentially expressed in healthy people with tuberculosis (27), mental illness (39) and autism (40). To the best of our knowledge, Song et al (14) first reported that the FAM135B gene is a tumor-associated gene for esophageal cancer, by whole-genome sequencing and other technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Many loci associated with mental retardation and brain function are found on the human X chromosome (Gécz et al 2009). We have previously shown an association of X-linked QTLs associated with maternal aggression in sows towards their young with puerperal psychosis in humans (Quilter et al 2007, 2012); this updated map of the pig X will make detecting significant loci and understanding their contribution to phenotypic traits far more robust in the future. These data also have relevance to the animal breeding industry; many of the QTLs mapped to the X chromosome are associated with production traits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of hypothalamic gene expression in the maternal infanticide model identified multiple genes, the expression of which was altered in pigs showing aberrant behaviour; several of these mapped to the previously-implicated QTL regions [of particular note were the HTR2C (serotonin receptor 2C), DRD2 (dopamine receptor 2) and PRL (prolactin) genes, the first two encoding antipsychotic drug targets[29]]. A genome-wide association study in this model indicated candidate regions on porcine chromosomes 3, 4 and 15, syntenic with human chromosomal regions implicated in bipolar disorder and postpartum psychosis (including 16p13)[30], whilst a candidate gene association study suggested preliminary evidence for association with oestrogen receptor ( ESR1 ), excitatory amino acid transporter 2 ( EAAT2 ) and dopamine receptor 1 ( DRD1 ) genes, but not HTR2C [31]. …”
Section: Current Approaches To Understanding Postpartum Psychosis Andmentioning
confidence: 96%